Financing Firms in Hibernation During the COVID-19 Pandemic - Didier, Tatiana (World Bank, Washington, DC, 2020)
The coronavirus (COVID-19) pandemic has imposed a heavy toll on economies worldwide, nearly halting economic activity. Although most firms should be viable when economic activity resumes, cash flows have collapsed, possibly triggering inefficient bankruptcies with long-term detrimental effects. Firms' valuable relationships with workers, suppliers, customers, governments, and creditors could be broken. Hibernation could slow the economy until the pandemic is brought under control and preserve those vital relationships for a quicker recovery. If all stakeholdersshare the burden of economic inactivity, firms are more likely to survive. Financing could help cover firms' reduced operational costs until the pandemic subdues. But financial systems are not well equipped to handle this type of exogenous and synchronized systemic shock. Governments could work with the financial sector to keep firms afloat, enabling forbearance as needed and absorbing part of the firms' increased credit risk, by implementing policies with proper incentives to keep firms viable.